2015
DOI: 10.26714/mki.5.1.2015.32-49
|View full text |Cite
|
Sign up to set email alerts
|

KEY SUCCESS FACTOR GOOD GOVERNMENT GOVERNANCE SERTA PENGARUHNYA TERHADAP KINERJA PEMERINTAH (Survey pada Pemerintah Kabupaten Gunungkidul)

Abstract: In this era, local government performance in Indonesia is weak because there are many abuse of authority everywhere, like corruption, collusion, and nepotism. Each of local government should apply the principles of good government governance in the government environtment, this is to improve performnace of local government. In this research good government governance principle contain transparancy, accountability, residents particpation, fairness, and responsibility. The purpose of this research is analyze dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
0
2
0
7
Order By: Relevance
“…Rusydi and Rossieta (2015) asserted that the implementation of the new public management is aimed to improve the efficiency and effectiveness of public services and its organizations. A strand of studies, Addink (2019); Lestiawan and Jatmiko (2016); Setyaningrum and Saragih (2019) suggested that application of the GPG will improve performance of public sector institutions. In addition, a study by examined the effect of GPG implementation on local government spending.…”
Section: Literature Review the Concept Of Good Public Governance (Gpg...mentioning
confidence: 99%
“…Rusydi and Rossieta (2015) asserted that the implementation of the new public management is aimed to improve the efficiency and effectiveness of public services and its organizations. A strand of studies, Addink (2019); Lestiawan and Jatmiko (2016); Setyaningrum and Saragih (2019) suggested that application of the GPG will improve performance of public sector institutions. In addition, a study by examined the effect of GPG implementation on local government spending.…”
Section: Literature Review the Concept Of Good Public Governance (Gpg...mentioning
confidence: 99%
“…Hasil lain juga dilakukan oleh yang hasilnya adalah transparasi berpengaruh terhadap kinerja instansi pemerintah yang dibutuhkan suatu instansi dalam memberikan informasi-informasi yang akan membuat kepercayaan pihak luas percaya kepada pemerintah dalam meningkatkan kinerja yang baik. Hasil ini juga sejalan dengan penelitian dikemukakan oleh Lestiawan dan Jatmiko (2015) keterbukaan informasi sangat penting bagi pemerintah dengan mendorong kinerja dalam penerapan program-program yang nantinya akan menjadi kegiatan yang dilakukan oleh pemerintah. Dari uraian di atas maka di simpulkan dalam hipotesis yaitu sebagai berikut: H2 : Prinsip Transparasi berpengaruh terhadap efektivitas kinerja pegawai pada Dinas Pertanian, Ketahanan Pangan dan Perikanan Kabupaten Ponorogo…”
Section: Pengaruh Prinsip Transparasi Terhadap Efektivitas Kinerja Pe...unclassified
“…Hasil dari Wahyuni Arifin dan Saiful Muchlis (2021) yang hasilnya akuntabilitas pegawai semakin meningkat dan keterbukaan penyelenggaraan urusan publik yang akan memudahkan dalam pengawasan agar terhindar dari penyelewengan atau penyalahgunaan wewenang, penelitian dari Lestiawan dan Jatmiko (2015) sejalan dengan hasil penelitian ini yaitu suatu prinsip akuntabel yang artinya bertanggungjawab terhadap hasil dari program yang dijalankan serta kebijakan-kebijakan yang telah ditentukan.…”
Section: Pengaruh Akuntabilitas Terhadap Efektivitas Kinerja Pegawaiunclassified
See 2 more Smart Citations